Thermal Properties of the Graphene Composites: Application of Thermal Interface Materials - Mohamed, Mazlan; Nazri Omar, Mohd; Shaiful Ashrul Ishak, Mohamad; Rahman, Rozyanty; Y.N, Zaiazmin; Ismael Rizman, Zairi (International Journal of Engineering and Technology, 2018)
Epoxy mixed with others filler for thermal interface material (TIM) had been well conducted and developed. There are problem occurs when previous material were used as matrix material likes epoxy that has non-uniform thickness of thermal interface material produce, time taken for solidification and others. Thermal pad or thermal interface material using graphene as main material to overcome the existing problem and at the same time to increase thermal conductivity and thermal contact resistance. Three types of composite graphene were used for thermal interface material in this research. The sample that contain 10 wt. %, 20 wt. % and 30 wt. % of graphene was used with different contain of graphene oxide (GO).Â The thermal conductivity of thermal interface material is both measured and it was found that the increase of amount of graphene used will increase the thermal conductivity of thermal interface material. The highest thermal conductivity is 12.8 W/ (mK) with 30 w. % graphene. The comparison between the present thermal interface material and other thermal interface material show that this present graphene-epoxy is an excellent thermal interface material in increasing thermal conductivity.Â Â